List of IMF Member Countries with Delays in Completion of Article IV Consultations or Mandatory Financial Stability Assessments over 18 Months. (Policy Papers; Policy Paper ;, 2019)
In accordance with Executive Board Decision No. 15106-(12/21), the Fund will publish on its external website a list of member countries whose Article IV consultations or mandatory financial stability assessments have been delayed by more than 18 months, as of December 15, 2019, since the expected deadline for conclusion.